Pengaruh Fasilitas dan Kualitas Pelayanan terhadap Kepuasan Pelanggan BUMDes Desa Betak Kecamatan Kalidawir Tulungagung - Mabtukha, Sahrotul; Suryaningsih, Tutut (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2024)
This research aims to determine the influence of facilities and service quality on customer satisfaction of BUMDes in Betak Village, Kalidawir District. There is a gap in this research. There is a research gap, namely regarding this research and previous research. This research is quantitative research. The population in this research is visitors to BUMDes Betak Village. In this research, non-probability sampling was used to determine the number of respondents using the random sampling method with 88 respondents. For the research method used, namely observation and questionnaires, the data analysis used was multiple linear regression. The research results showed that. The results of this research show the influence of service quality on customer satisfaction of BUMDes des Betak, Kalidawir Tulungagung District. This is proven by tcount > ttable 6.345 > 1.988 and significant 0.000 < 0.05. So H0 is rejected, H1 is accepted, there is a significant influence on facilities (X1), there is an influence on customer satisfaction of BUMDes, Betak Village, Kalidawir Tuungagung District. There is an influence of service quality (X2) which has a value of tcount > ttable, namely 3.830 > 1.988 and a significant value of 0.000 < 0.05, so H0 is rejected. H1 is accepted, which means there is a significant influence of service quality (X2) on customer satisfaction of BUMDes in Betak Village, Kalidawir District. Tulungagung This shows that 70.7% of the change in the customer satisfaction variable (Y) is influenced by the facility variable (X1) and service quality (X2) while the remaining 29.3% is influenced by other factors outside the facility variable (X1) and service quality. (X2).